Urgensi Identifikasi Potensi Akademik dalam Mendukung Kesesuaian Pilihan Program Studi Mahasiswa - Mufida Istati; Nurul Rahmi; Ermalianti Ermalianti; Alfina Lailan (YASIN, 2026)
The identification of academic potential plays an important role in helping prospective students choose study programs that are aligned with their interests and personal characteristics. However, previous studies have generally positioned academic potential assessment more as an instrument for predicting learning success, whereas studies that integrate assessment results with students’ experiences in undertaking their study programs remain limited. This study aims to analyze the urgency of identifying academic potential in supporting the suitability of students’ study program choices. This study used a sequential explanatory mixed methods design. In the quantitative stage, the Rothwell Miller Interest Blank (RMIB) test was administered to 97 students from five faculties at Universitas Islam Negeri Antasari Banjarmasin to map their interest profiles. In the qualitative stage, semi-structured interviews were conducted with 20 students selected purposively to explore their experiences related to study program selection and the alignment of their interests with the field of study they were pursuing. Quantitative data were analyzed descriptively, whereas qualitative data were analyzed thematically. The results show that students had diverse interest profiles and that not all of them were aligned with the study programs they had chosen. Students who pursued study programs aligned with their interests tended to show more positive academic experiences, whereas misalignment of interests had the potential to create obstacles in motivation and academic adaptation. The conclusion of this study affirms that the identification of academic potential is important to use as a basis for making more appropriate educational decisions for prospective students. The implications of this study indicate the need for the systematic use of interest assessments in academic guidance services and study program selection in higher education.